Menakar Liberalitas Pemikiran al-Tufi tentang Maslahah dalam Hukum Islam - Bahri, Syaiful (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2015)
This paper attempts to discuss Najmuddin al-Tufi’s thought on maslahah, as well as see the extent of his liberal idea. In order to unravel this problem, the author conducted a literature review to examine al-Tufi’s work, Risalah fi Ri’ayah al-Maslahah. This study resulted in two conclusions. First, al-Tufi’s thought on maslahah is quite controversial because it is delivered with provocative words. Al-Tufi states that in case of conflict between nas and masalahah, the precedence is maslahah using Takhsis and Tabyin mechanisms. Second, al-Tufi’s thought can’t be put into the category of liberal thought. Since, although al-Tufi states the permissibility displacing the position of nas with maslahah, the process must be carried out with the Takhsis and Tabyin mechanisms which are already popular practiced in Islamic Legal thoughts.Keywords: Al-Tufi, Maslahah, Ri’ayah al-Maslahah